1996
DOI: 10.1016/0376-7388(95)00068-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions during membrane formation of polylactides. I. A morphological study of membranes obtained from the system polylactide-chloroform-methanol

Abstract: The influence of solid-liquid demixing, liquid-liquid demixing and vitrification on the morphology of polylactide membranes has been investigated. To study the effects of crystallization of polylactides on the membrane formation and morphology, polylactides of varying stereoregularity were used. The polymers applied were poly-L-lactide (PLLA) and copolymers with different molar ratios of L-lactide and I>lactide [poly-L95/D5-1actide (PLA95), poly-L80/D20-1actide (PLA80) and poly-L50/D50-1actide (PDLLA) ]. Solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 26 publications
2
43
0
5
Order By: Relevance
“…This is consistent with observation that, although crystallization may be thermodynamically favorable, the kinetically favored liquid᎐liquid demixing process often dominates the resulting polymer morphology, even for rapidly crystallizing polymers such as L-PLA Ž . van de Witte et al, 1996 . However, the precipitation mechanism is difficult to evaluate directly from crystallinity because of the potential for solvent or CO -induced crystalliza-2 Ž .…”
Section: Microparticle Formation and Characterizationmentioning
confidence: 98%
“…This is consistent with observation that, although crystallization may be thermodynamically favorable, the kinetically favored liquid᎐liquid demixing process often dominates the resulting polymer morphology, even for rapidly crystallizing polymers such as L-PLA Ž . van de Witte et al, 1996 . However, the precipitation mechanism is difficult to evaluate directly from crystallinity because of the potential for solvent or CO -induced crystalliza-2 Ž .…”
Section: Microparticle Formation and Characterizationmentioning
confidence: 98%
“…If neither of these transitions occurs, liquid-liquid demixing will proceed until two completely separated layers are obtained. 11 Since PDLLA cannot crystallize, 11,22 and its glass transition line does not cross the binodal for either methanol or water (this Table I. is illustrated in Fig. 4), it will not be solidified but will collapse given sufficient time.…”
Section: Pdlla Films: Nonsolvent Effectsmentioning
confidence: 97%
“…For a film made out of 5% w/w PDLLA/chloroform, which was immersed and kept in methanol for 1 day or longer, Van de Witte et al 11 found that no structure was preserved. Comparison with our results shows that increasing the polymer concentration reduces the time required for phase separation, and results in faster loss of structure.…”
Section: Pdlla Films: Nonsolvent Effectsmentioning
confidence: 99%
See 2 more Smart Citations